Simulation design of uniform low turn-on voltage and high reverse blocking AlGaN/GaN power field effect rectifier with trench heterojunction anode. (May 2017) - Wang, Fangzhou; Chen, Wanjun; Wang, Zeheng; Sun, Ruize; Wei, Jin; Li, Xuan; Shi, Yijun; Jin, Xiaosheng; Xu, Xiaorui; Chen, Nan; Zhou, Qi; Zhang, Bo
Abstract: To achieve uniform low turn-on voltage and high reverse blocking capability, an AlGaN/GaN power field effect rectifier with trench heterojunction anode (THA-FER) is proposed and investigated in this work which includes only simulated data and no real experimental result. V T has a low saturation value when trench height ( H T ) is beyond 300 nm, confirming it is possible to control the V T accurately without precisely controlling the H T in the THA-FER. Meanwhile, high H T anode reduces reverse leakage current and yields high breakdown voltage ( V B ). A superior high Baliga's Figure of Merits (BFOM = V B 2 / R on, sp, R on, sp is specific-on resistance) of 1228 MW/cm 2 reveals the THA-FER caters for the demands of high efficiency GaN power applications. Highlights: An AlGaN/GaN power field effect rectifier with trench heterojunction anode (THA-FER) is presented by simulation. Turn-on voltage has a low saturation value when trench height is beyond 300 nm. High trench height anode contributes to suppress leakage current and improves breakdown voltage. A high BFOM of 1228 MW/cm 2 shows significant potential of the THA-FER in high efficiency GaN power applications.